IMF Policies and Nigeria’s Relationship : Lending Preconditions From 2019 To 2024. - Sulaiman T.H; Ajiteru,S.A.R; Abalaka, J.N (International Forum of Researchers and Lecturers, 2025)
Nigeria's economy has been severely stagnant since the 1980s. Afrocentric literature charts the nation's history, whereas Eurocentric literature identifies the Nigerian civil war and the corrupt practices of its leaders as the primary cause economic hardships to her historical colonial dominance and economic exploitation activities. However, none of the aforementioned reasons provide stronger support for being the cause of the nation's economic dysfunction, particularly when contrasted with IMF measures implemented there. The IMF's policies on Nigeria's Structural Adjustment Program (SAP) and its Loan Conditionality are partially shown in this article to be